An Italian Disease-Based Registry of Axial and Peripheral Spondyloarthritis: The SIRENA Study - Zabotti, Alen; Luchetti, Michele Maria; Selmi, Carlo Francesco; Ramonda, Roberta; Grembiale, Rosa Daniela; Dagna, Lorenzo; D'Angelo, Salvatore; Cafaro, Giacomo; De Vita, Salvatore; Felicetti, Mara; Marelli, Silvia; Frigerio, Daniela; et al. (Frontiers in Medicine, 2021)
Introduction: Data about the clinical presentation and management of early and mild spondyloarthritis (SpA) are limited. Objectives: The objective of this study was to describe the baseline characteristics of disease-modifying antirheumatic drug (DMARD)-naïve patients with axial or peripheral SpA. Methods: The Spondyloarthritis Italian Registry: Evidence from a National Pathway (SIRENA) study is an ongoing, Italian, multicenter, prospective registry of patients with a first or newly confirmed diagnosis of SpA according to the Assessment of SpondyloArthritis International Society (ASAS) criteria. To be included, patients had to be naïve to conventional, targeted, and biological DMARDs for SpA. Patients were enrolled between June 2017 and June 2019 and classified into groups according to disease presentation: predominantly axial or peripheral manifestations. The study is ongoing, and patients are being followed for 2 years, with an evaluation every 6 months according to clinical practice. Differences in baseline demographics, lifestyle, and clinical characteristics between axial and peripheral SpA were evaluated. Results: In this study, 350 patients were enrolled, of which 123 (35.1%) were axial and 227 (64.9%) were peripheral patients. Patients with axial SpA were significantly younger at enrollment (median age: 44 vs. 53 years), had significantly more anxiety/depression (13 vs. 2.6%), and expressed higher disease activity compared to patients with peripheral SpA. Patients with peripheral SpA had significantly more cardiometabolic disorders (33 vs. 18.7%), skin psoriasis (65.2 vs. 21.1%), and nail psoriasis (35.5 vs. 17.1%) than patients with axial SpA. Dactylitis, enthesitis, and fibromyalgia were observed, respectively, in 17.6, 51.2, and 5.7% of patients with axial SpA and 24.3, 40, and 3.1% of patients with peripheral SpA. In both disease groups, women tended to report depression, joint tenderness, and higher disease activity more frequently than their male counterparts. At inclusion, a new diagnosis of SpA was performed in 58% of axial and 77% of peripheral patients, with a median time from symptom onset to diagnosis of 36 and 24 months, respectively. At baseline, most patients with axial SpA (77%) started a biological DMARD, while over half of the peripheral patients started a conventional DMARD. Conclusions: Based on a well-characterized clinical registry of SpA, we provided real-world insights on the clinical features of DMARD-naïve SpA patients, pointing out major differences between axial and peripheral disease in terms of clinical characteristics and treatment pattern. Future prospective evaluations within the SIRENA study will improve knowledge on SpA and contribute to defining the best therapeutic approach.